Utilization of Blacu Fabric Material Waste as an Alternative Material for Fast Fashion Products - Cucu Nuraeni; Dian Widiawati (PT Publikasiku Academic Solution, 2023)
In today's fast fashion era, the fashion industry has experienced many developments supported by technological advances in the current digital era accelerating the development process in the fashion industry. In addition, the fast fashion trend is also bad for the environment, continuous product production even tends to increase the fast fashion trend produces large textile waste and requires a long time in the decomposition process. Therefore, the purpose of this study is to find out what the utilization of Blacu fabric waste produced by the fashion industry looks like. This research uses qualitative research methods with an exploratory study approach which is a good method to collect information about the perception of entrepreneurial intentions. The result of this study is that Blacu fabric waste can be reused and become an alternative material for making fast fashion in the form of bag bags or tote bags, the utilization is done using the upcycling method and patchwork processing method, this is because the production costs are economical when compared to other fabric waste processing techniques and produce product textures that have distinctive characteristics because they go through the process of preparation and sewing between fabrics